Lattices of Dielectric Resonators - Trubin, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides the analytical theory of complex systems composed of a large number of high-Q dielectric resonators. Spherical and cylindrical dielectric resonators with inferior and also whispering gallery oscillations allocated in various lattices are considered. A new approach to S-matrix parameter calculations based on perturbation theory of Maxwell equations, developed for a number of high-Q dielectric bodies, is introduced. All physical relationships are obtained in analytical form and are suitable for further computations. Essential attention is given to a new unified formalism of the description of scattering processes. The general scattering task for coupled eigen oscillations of the whole system of dielectric resonators is described. The equations for the  expansion coefficients are explained in an applicable way. The temporal Green functions for the dielectric resonator are presented. The scattering process of short pulses in dielectric filter structures, dielectric antennas  and lattices of dielectric resonators is discussed.  .
Natural Oscillations of Coupling Dielectric Resonators- Multi- Filters on Lattices of Dielectric Resonators -- Scattering of Electromagnetic Waves on Lattices of Dielectric Resonators in the Open Space -- Antenna Structures on Lattices of Dielectric Resonators -- Scattering of Electromagnetic Pulses on Lattices of Dielectric Resonators --  Conclusions.
Keywords: Telecommunication; Semiconductors; Optical materials; Microwaves, RF Engineering and Optical Communications; Semiconductors; Optical Materials